Tesso Nilo Buffer Zone: A Space of Ecofeminism, Women, Ecology, and Social Resilience - Mita Rosaliza; Yusmar Yusuf; Hesti Asriwandari; Robi Armilus (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
This article examines the buffer zone of Tesso Nilo National Park as an ecofeminist arena where interactions among women, ecology, and social resilience evolve amid deforestation, encroachment, and contested land use. Addressing research gaps that marginalize indigenous women’s conservation roles, the study explores how Batang Nilo women perform forest guardianship and sustain local ecological balance. Employing a qualitative participatory method in several buffer zone villages, twelve indigenous women involved in resource management participated through interviews, focus groups, observations, and participatory mapping. Guided by a local ecofeminist perspective, thematic analysis reveals that women’s forest patrols, cultivation of native and medicinal plants, non-timber forest product use, and community-based eco-tourism actions embody a politics of care. These practices reinforce socio-ecological resilience and advocate for gender-inclusive spatial governance that acknowledges women not merely as beneficiaries but as pivotal ecological agents in sustaining forest life.